Determining The Feed Value, Feed Quality, and in Vitro Fermentation Properties of Italian Ryegrass (Lolium multiflorum L.) Harvested in Different Periods - Esra Gürsoy; Gürkan Sezmiş; Ali Kaya (Turkish Journal of Agriculture: Food Science and Technology)
The purpose of this study was to determine the chemical content, in vitro gas and methane production, relative feed value (RFV), relative feed quality (RFQ), in vitro digestibility parameters, and microbial protein production of the Italian ryegrass plants harvested in different periods of the 2020 production season in Erzincan. In this study an ANKOM Daisy Incubator was used to determine the in vitro digestibility parameters. In vitro gas production technique was used todetermine gas production and predicted parameters. It was found that there were significant differences between the Italian ryegrass plants harvested in different periods in terms of composition, RFV, RFQ, and in vitro digestibility and fermentation parameters. The RFV, metabolizable energy (ME), net energy (NE), true NDF digestibility (TNDFD), organic matter digestibility degree (OMDD), total digestible nutrient (TDN), dry matter intake (DMI), and RFQ values of the Italian ryegrass plants were found to be 247.32, 9.13, 5.68, 62.26%, 54.15%, 55.35%, 4.82%, and 215.81, respectively. On the other hand, after 24 hours of incubation it’s in vitro gas (GP), and methane production (ml and %), true dry matter digestibility (TDMD) values, partitioning factor (PF), microbial protein (MP), microbial protein synthesis efficiency (MPSE), and true digestibility (TD) were found to be 105.41, 17.35, 16.42, 281.72, 2.68, 57.68, 20.32, and 59.82, respectively. In conclusion, determining the digestibility of plants via the measurement of RFV, RFQ, digestion parameters, and gas production in different harvest periods provided insights into the potential of Italian ryegrass as a feed material.